Educational research for classroom teachers. - Barnes, John B. (The Putnam series in education, 1960)
"In this book, the author introduces the reader to a kind of research that is teacher-oriented and to a kind of teaching that is research oriented. The book serves the general field of educational research in terms of its basic methods and techniques then, importantly, shows three large areas of educational work in which research may be applied: --the study of individuals --the study of classroom groups or subgroups --the study of teaching and learning problems. Each of these areas is illustrated by real cases which open up practical ways to apply research techniques to the study of many kinds of teacher-administrator problems"--Jacket. (PsycINFO Database Record (c) 2013 APA, all rights reserved).